JAK inhibitors in systemic juvenile idiopathic arthritis - He, Tingyan; Xia, Yu; Luo, Ying; Yang, Jun (Frontiers in Pediatrics, 2023)
Objective: Systemic juvenile idiopathic arthritis (SJIA) is characterized by excessive and inappropriate production of pro-inflammatory cytokines. In this study, we aimed to assess the efficacy and potential adverse effects of JAKi in SJIA patients. Methods: Patients with SJIA who received JAKi and underwent at least one assessment of efficacy and safety after JAKi initiation were eligible for this study. Data were collected retrospectively from inpatient or outpatient medical records at JAKi initiation; months 1, 3, 6, 9, and 12; disease flare; JAKi discontinuation; or the last follow-up. Results: Ten patients with SJIA were included in the study. At the start of JAKi treatment, all patients presented with active disease; five showed variable adverse effects secondary to corticosteroids. Seven patients received tofacitinib (one later switched to ruxolitinib). Of these, only two patients showed a complete response of persistent arthritis in association with tocilizumab; two showed a partial response; three were non-responders. Four patients with SJIA-MAS or persistent hyperferritinemia were treated with ruxolitinib. Ruxolitinib allowed a good response on MAS parameters in three patients. All these four patients required an adjunction or switch to canakinumab later. The median decrease in the daily corticosteroid dose between JAKi initiation and the last follow-up was 90.6% in patients with complete remission and 77.4% in other patients. Three patients discontinued corticosteroid treatment. Severe adverse events were not observed during JAKi treatment. Conclusions: JAKi may be an alternative or adjuvant agent for SJIA patients, especially in those with persistently active disease, corticosteroid-related adverse reactions, or SJIA-MAS.